Identidade, ensino de História e educação escolar quilombola: reflexões históricas a partir de uma escola quilombola urbana na comunidade de Paratibe/João Pessoa-PB (c. 2012-2020) - Holanda, Nadiane Chaves Pereira de (2021)
Despite the existence of Law No. 10.639, of January 9, 2003, which makes the teaching of African and Afro-Brazilian History and Culture mandatory in elementary and high schools, and of Resolution No. 8, of November 20, 2012, that defines the National Curriculum Guidelines for Quilombola School Education in Basic Education, the educational reality of quilombola schools is still marked by a teaching that does not fully articulate school knowledge to the daily life and history of the community. As a result, they reinforce the existing silences regarding the culture and identity of these remaining quilombola groups. Reflecting on this issue and realizing the need to implement pedagogical practices that develop the specificities of Quilombola School Education in the environment of the Municipal Elementary School Prof. Antônia do Socorro Silva Machado, located in Paratibe, João Pessoa - PB, we developed this search. In this way, we hope to contribute to the development of a curriculum aimed at Quilombola School Education and that establishes references of belonging and identity for the community of Paratibe. In addition, we aimed to value and preserve memory and identity, through oral testimonies and sample narratives, from students and local leaders. We also take into account the questions raised by teachers and management about teaching practice and about the challenges for implementing specific education for the residents of Quilombo de Paratibe. This study was characterized as a field research with qualitative investigation, historical complementary method and bibliographical and documentary technique, carried out through the study of the National Curriculum Guidelines for Quilombola School Education and the Political-Pedagogical Projects - PPP (2014-2020) from that school, in addition to the dialogue with works and authors who addressed and enriched the theme. As a product, an online page was created called Paratibe: history and resistance_ the teaching of history and quilombola school education, capable of respecting and valuing the culture, customs and traditions of the local quilombola peoples and which helps in the development of educational practices aimed at combating racial prejudice and at valuing the ethnic identity of the community in Paratibe-PB.